ENDOTHELIAL FUNCTION IS ASSOCIATED WITH TRIPLE SIGNAL IN FIBROMUSCULAR DYSPLASIA: THE MEDYA STUDY. (June 2018) - Bruno, R.M.; Marais, L.; Khettab, H.; Boulanger, C.; Jeunemaitre, X.; Plouin, P.; Laurent, S.; Boutouyrie, P.; Azizi, M.
Abstract : Objective: Triple signal (TS) is a subclinical lesion were found in the common carotid artery of individuals with renal fibromuscular dysplasia (FMD), However, the mechanisms underlying this alteration in FMD patients are still unknown and might involve endothelial and/or smooth muscle cell dysfunction. We aimed at investigated whether FMD or triple signal, is associated with systemic vascular dysfunction. Design and method: The MEDYA study is a case-control, cross-sectional study, enrolling 47 individuals with renal FMD, 47 matched individuals with essential hypertension (HT) and 50 healthy controls (C). All individuals underwent an assessment of endothelium-dependent dilation (EDD) of the brachial artery by the flow-mediated dilation technique and endothelium-independent dilation (EID) by sublingual administration of glyceryl trinitrate 150 mcg. EDD and EID were allometrically corrected for baseline diameter. Triple signal score was also computed in the common carotid arteries bilaterally, based on B-mode and RF images. A cut-off of 8 was used to discriminate TS carriers. Results: FMD, but not HT, showed impaired EID in comparison to controls (p = 0.003). FMD (but not TS) was among the determinants of EID_corr in a multiple linear regression model (beta = −0.03, p = 0.005). TS prevalence (FMD 48.9%, HT 31.9%, C 16.0%) was higher in FMD than in C (p < 0.001), but tended to be increased in HT as well (p = 0.07). In a multiple logistic regression model adjusted for confounders, FMD (OR 4.54, CL95% 1.56–13.23) but not HT, was independently associated with TS. In the FMD subgroup, TS was associated with older age, higher peak shear stress and lower EDD. EDD was still reduced in FMD patients with TS after correction for confounders (1.14 ± 3.59 vs 3.55 ± 4.18, p = 0035). In the HT subgroup, TS was independently associated only with older age and hypercholesterolemia. Conclusions: FMD is characterized by impaired smooth muscle cell function and increased TS prevalence, subclinical alterations independent from each other. TS might have a different pathophysiological significance in FMD and HT. Indeed, among FMD patients TS is associated with impaired endothelial function. Conversely, in HT TS seems to be associated only with classical CV risk factors.